Single-crystalline Ge₁₋ₓSnₓ/Si p–n heterojunction photodiodes with Sn compositions up to 10% - An, Shu (2023)
GeSn/Si heterojunction photodiodes are attractive because they can extend light detection wavelength range. However, the development of such photodiodes via epitaxial growth faces great challenges due to unavoidable issues such as lattice and thermal mismatches between Si and GeSn. Here, print Si nanomembranes are transferred on GeSn/Ge/Si substrates to form the GeSn/Si heterojunction photodiodes. The p-Ge0.977Sn0.023/n-Si heterojunction photodiodes exhibit a good rectifying behavior with a low dark current density of 40 mA cm−2 and responsivity of 0.41 A W−1 at 1550 nm under a reverse bias of −2 V. In addition, the detection wavelength range of p-Ge0.9Sn0.1/n-Si is extended to 2100 nm because of the increased Sn composition. The bandgap calculation of as-grown GeSn with various Sn compositions is carried out. It confirms that the enhanced responsivity and extended detection wavelength ranges are attributed to the reduced bandgap from 750 to 601 meV when the Sn composition is increased from 2.3% to 10%. The result shows that the transfer printing of a freestanding single-crystalline Si nanomembrane to a bulk GeSn/Ge/Si substrate can provide an excellent alternative route for realizing GeSn/Si heterojunction photodiodes.